2016
DOI: 10.1590/s1806-92902016000900002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of eggshell colour and spot area in Japanese quails: II. Slaughter and carcass characteristic

Abstract: -This study was carried out to investigate the effects of eggshell colour and spot properties (colour and size of the spot area) on growth performance and carcass traits of Japanese quail (Coturnix coturnix japonica) eggs. Study material were allocated to five groups according to their eggshell and spot colours: black spots on greyish white coloured eggshell (I), blue spots on greyish white coloured eggshell (II), diffuse brown spots on greyish brown coloured eggshell (III), brown spots on light green colored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(19 reference statements)
0
2
1
Order By: Relevance
“…In the study of Kahksar et al (2012) on the effects of essential thyme oil dietary supplementation on the performance and blood parameters of Japanese quails, obtained 159g body weight in the control group and 169 g the bird fed thyme essential oil. Alasahan et al (2016) found an average body weight in 5-week-old quails of 215.77 g, whereas Bonos et al (2010) reported 172-180.8 g. The body weight values reported in those studies for 5-and 6-week-old quails are lower than those obtained in the present study when quails were still 4 weeks old. In addition, 5-week body weight values were found to be considerably higher than those obtained in the aforementioned studies.…”
Section: The Effects Of Using Garlic Extract For Quail Hatching Egg Dcontrasting
confidence: 72%
“…In the study of Kahksar et al (2012) on the effects of essential thyme oil dietary supplementation on the performance and blood parameters of Japanese quails, obtained 159g body weight in the control group and 169 g the bird fed thyme essential oil. Alasahan et al (2016) found an average body weight in 5-week-old quails of 215.77 g, whereas Bonos et al (2010) reported 172-180.8 g. The body weight values reported in those studies for 5-and 6-week-old quails are lower than those obtained in the present study when quails were still 4 weeks old. In addition, 5-week body weight values were found to be considerably higher than those obtained in the aforementioned studies.…”
Section: The Effects Of Using Garlic Extract For Quail Hatching Egg Dcontrasting
confidence: 72%
“…The previous studies [26,27] have also confirmed that eggshell color is a genetic transformation of pigments on the egg surface in the uterus. In addition, Alasahan et al [28] classified the color of eggshells into five different groups, including black-spotted gray-white, green-spotted gray-white, scattered brown-spotted gray-brown, brown-spotted light-green, and small brown-spotted gray-brown. However, they also indicated that the effect of eggshell color on egg weight, eggshell mass, albumen weight, and yolk weight was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study, the female quails had higher body weight than male quails, and the best body weight gain was in the GF2 and GF4 groups in females and the GF4 group in male quails compared to the control group. The fact that female quails have better growth rates than male quails is a predominant factor in breeding female-male quails together in meat production (16)(17)(18)(19). In addition, Sarica et al (20) reported that the live weight of male quails that were left out of breeding increased until the eighth week and then decreased, but it was not considered a significant change.…”
Section: Discussionmentioning
confidence: 99%